Agricultural extension services and gender equality: An institutional analysis of four districts in Ethiopia - Cohen, Marc J.; Lemma, Mamusha (International Food Policy Research Institute, 2011)
Decentralized delivery of public services has been promoted as a means to enhance citizen voice and make service provision more responsive to users. Ethiopia has undertaken two rounds of decentralization, making first the regional states and then the district governments responsible for providing key public services. This paper explores whether decentralization has improved the quality of service delivery and citizen satisfaction with the services provided, focusing on agricultural extension. Specifically, we examine whether services are responsive to the needs and expressed demands of poor farmers, including women farmers. We focus on the institutional arrangements through which agricultural extension services are provided and how these contribute to efficiency, effectiveness, and equity in service delivery. We carried out qualitative research on these questions in four districts in four different regional states. We interviewed district government officials, community leaders, and representatives of civil society organizations, and carried out focus group discussions with men and women farmers. In all, we interviewed 105 people.